Study of initial stage of mechanochemical transformation in pyrite - Paneva D.; Mitova D.; Manova E.; Kolev H.; Kunev B.; Mitov I. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The initial stage of transformation of pyrite to Fe(II)-sulfate as a result of mechanical milling is studied by X-ray powder diffraction (XRD), Moessbauer spectroscopy (MS), Infrared (IR) and X-ray photoelectron spectroscopy (XPS) techniques. A degree of conversion of 0.071 is achieved in the time interval of 0 36 min. The kinetic data satisfy the equation of a shrinking core reaction 1-(1-α)1/3=kt. The reaction is of the first order. The calculated rate constant is k=6.434.10-4 min-1. .